Improve the Teachers’ Skill in Design Learning Trough the Empowering of MGMP and the Performance Motivate - Alhafif Syahputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The science teachers’ skill in designing learning are very low in pematangsiantar. The teachers’ performance motivate are also rarely measured. So far the method that used to give the instruction for teachers’ are conventional method. The aim of the research to know the improvement of science teachers’ skill in desaign learning through empowering MGMP and performance motivate. This is an experimental research with 2 x 2 factorial design. This research have done among the junior high school science teachers’ in Pematangsiantar. With the total number of studied are 24 persons. The result of the research show that : 1) There are the difference the teachers’ skill in design science learning with creative and copying method, 2) There are the difference of the teachers’ skill. In design science learning betmeen those who hare high performance motivate with the low one, 3) There are the interaction between the guidance method and performance motivate, 4) The teacher who have high performance motivate that used the creativy method give higher scores in design science learning than used copying method, and 5) The teacher who have low performance motivate that used the copying method give higher scores in design science learning than used creativy method.